QUANTIFICATION OF THE RELATIONSHIP BETWEEN SATURATEDAND UNSATURATED FATTY ACIDS IN YOGURT PRODUCED INTUNGURAHUA PROVINCE, ECUADOR - Pérez Aldás, Lander Vinicio; Córdova Culqui, Mercedes Elizabeth; Delgado Ramos, Andrea Verónica (Tierra Infinita, 2023)
Dairy products, especially yogurt, are categorized as indispensable food products in the Ecuadorian daily diet. This drink contains essential nutrients for the human body, including proteins, minerals, fat, carbohydrates, fiber, and vitamins, which together generate energy and vitality for consumers. The main objective of this study was to determine the relationship between saturated fatty acids (SFA) and unsaturated fatty acids (UFA) in yogurt made in the province of Tungurahua and establish its possible effect on cardiovascular disease. The determination of the lipid profile of yogurt was performed by gas chromatography coupled to mass spectrophotometry, the main fatty acids being; myristic acid (10.8% ±0.5), palmitic acid (37.0 % ±1.6), oleic acid (10.7% ± 0.4) and stearic acid (25.1% ±0.5), highlighting that in some yogurt samples there was the presence of conjugated linoleic acid with an average value of (0,2 % ± 0.4). Regarding the nutritional quality indices, the values of the (SFA/UFA) ratio, ω6/ω3, and atherogenicity index were 2.0% ± 1.0; 4.4 % ± 6.1% and 2.5 % ± 1.3%, respectively. The lipid profile comprised SFA/UFA, which ranged from 1.2 % to 3.0 %, indicating that yogurt has a positive effect on the nutritional contribution of the consumer in individual places in the province of Tungurahua.